Effiziente maßgeschneiderte Wärmebehandlung von Blechhalbzeugen in der Serienfertigung - Kahrimanidis, Alexander; Lechner, Michael; Wortberg, D.; Merklein, Marion (wt Werkstattstechnik - Online, 2015)
LFT Import::2019-07-29 (2119)

Thermisch unterstützte Umformung von Aluminiumblechen - Kahrimanidis, Alexander (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2016)
The formability of aluminum alloys can be extended by using tailor heat treated blanks (THTB). This book gives an introduction to the basics of producing complex part geometries with THTB and demonstrates how the technology can be used in an industrial application by manufacturing an outer skin part of a passenger car. Thereby the book presents a holistic approach for the production and processing of THTB that can be transferred to any other part geometr